Ethnic minority and their knowledge about their human health rights: evidence from a national survey in Peru - Uyen-Cateriano, Angela (2024)
Purpose: This study aims to evaluate the association between ethnic minority membership and their knowledge about their human health rights in Peru. Design/methodology/approach: A secondary analysis of the National Health User Satisfaction Survey 2015–2016 was conducted using an analytical cross-sectional design. Participants who spoke Quechua, Aymara, Awajun, Bora or a language other than Spanish aged 15 year were considered as a racial minority. The question “Do you know that by law you have health rights?” was applied to incorporate knowledge on health rights. Generalized linear models of the Poisson distribution were used to calculate crude prevalence ratio and adjusted prevalence ratio. A total of 3,721 responses were included in the analysis. Findings: The average age was 38.3 year, and 26.6% were males. The prevalence of belonging to an ethnic minority was 7.7%, and 27.6% of the participants did not know about their health rights. An association was found in the adjusted regression analysis between belonging to an ethnic minority and a greater probability of not knowing human health rights. Originality/value: The value of the works lies in one in four participants who did not know he had health rights by law. Belonging to an ethnic minority was associated with not knowing about having human health rights.